Green Marketing, Brand Image dan Kualitas Produk: Faktor Kunci dalam Keputusan Pembelian The Body Shop di Surabaya - Galuh Kinanti; Supriyono; Reiga Ritomiea Ariescy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the current era of globalization, global warming is one of the most frequently discussed environmental pollution problems. One of the main problems facing the world today is global warming. The influence of green marketing helps reduce the impact of global marketing, with the presence of green marketing indicating a change in people's behavior in consuming and using certain goods or services. One company that has implemented the green marketing concept with the aim of reducing the negative impact of plastic waste is The Body Shop. This research aims to evaluate the influence of Green Marketing, Brand Image, and Product Quality on Purchasing Decisions for The Body Shop in Surabaya. Data was collected through questionnaires distributed online using Google Forms to respondents. A total of 108 respondents from The Body Shop consumers in Surabaya participated in this research. The analysis technique used is a component-based SEM method with the smartPLS application. The research results show that Green Marketing has no influence on Purchasing Decisions, while Brand Image and Product Quality have a positive and significant influence on Purchasing Decisions for The Body Shop in Surabaya.